Single-dose radiosurgical treatment for hepatic metastases - therapeutic outcome of 138 treated lesions from a single institution - Habermehl, Daniel; Herfarth, Klaus K.; Bermejo, Justo Lorenzo; Hof, Holger; Rieken, Stefan; Kuhn, Sabine; Welzel, Thomas; Debus, Juergen; Combs, Stephanie E. (Radiation Oncology, 2013)
Background: Local ablative therapies such as stereotactically guided single-dose radiotherapy or helical intensity-modulated radiotherapy (tomotherapy) with high single-doses are successfully applied in many centers in patients with liver metastasis not suitable for surgical resection. This study presents results from more than 10 years of clinical experience and evaluates long-term outcome and efficacy of this therapeutic approach.Patients and methods: From 1997 to 2009 a total of 138 intrahepatic tumors of 90 patients were irradiated with single doses of 17 to 30 Gy (median dose 24 Gy). Median age of the patients was 64 years (range 31-89 years). Most frequent underlying tumor histologies were colorectal adenocarcinoma (70 lesions) and breast cancer (27 lesions). In 35 treatment sessions multiple targets were simultaneously irradiated (up to four lesions at once). Local progression-free (PFS) and overall survival (OS) after treatment were investigated using uni- and multiple survival regression models.Results: Median overall survival of all patients was 24.3 months. Local PFS was 87%, 70% and 59% after 6, 12 and 18 months, respectively. Median time to local progression was 25.5 months. Patients with a single lesion and no further metastases at time of RT had a favorable median PFS of 43.1 months according to the Kaplan-Meier estimator. The type of tumor showed a statistical significant influence on local PFS, with a better prognosis for breast cancer histology than for colorectal carcinoma in uni- and multiple regression analysis (p = 0.05). Multiple regression analysis revealed no influence of planning target volume (PTV), patient age and radiation dose on local PFS. Treatment was well tolerated with no severe adverse events.Conclusion: This study confirms safety of SBRT in liver lesions, with 6- and 12 months local control of 87% and 70%. The dataset represents the clinical situation in a large oncology setting, with many competing treatment options and heterogeneous patient characteristics. © 2013 Habermehl et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2023-03-08